Determinants of adequate antenatal care visits among pregnant women in low-resource setting: evidence from Tanzania national survey - Elihuruma Eliufoo; Victoria Majengo; Yusheng Tian; Deogratius Bintabara; Fabiola Moshi; Yamin Li (BMC Pregnancy and Childbirth)
Abstract Background Antenatal care (ANC) plays a crucial role in reducing maternal fatalities and morbidities through early detection and management of pregnancy-related complications and ensures the proper referral in the level of care. Various variables facilitate a pregnant woman’s ability to schedule enough ANC visits. This research sought to identify factors contributing to Tanzanian pregnant women receiving adequate antenatal care. Methods The study used data from the 2015-16 TDHS-MIS. We analysed a total of 6924 included in the analysis. The outcome variable was adequate ANC, and we assessed different predictors on how they influence good antenatal care attendance. Bivariate (chi-square) and multivariate logistic regression were conducted at the statistical significance of p < 0.05. Results 3438 (49.7%) had inadequate ANC visits. Determinants for antenatal attendance included giving birth outside health facility (aOR = 0.77, 95%CI = 0.62–0.95, p-value = 0.02) are less likely to complete all the ANC, mothers who book early for ANC (aOR = 5.79, 95%CI = 4.56–7.35, p-value < 0.001) were more likely to achieve the recommended visits, parity of 2 to 4 (aOR = 0.63, 95%CI = 0.48–0.81, p-value < 0.001), and five and above (aOR = 0.48, 95%CI = 0.35–0.68, p-value < 0.001) showed a decreased odd to complete adequate ANC, the use of the Internet (aOR = 1.62, 95%CI = 1.08–2.42, p-value = 0.02) were two times more likely to attend the required visits, pregnant mothers who experienced sexual violence from partners (aOR = 0.70, 95%CI = 0.52–0.94, p-value = 0.02) were less likely to complete the adequate visit, and the use of the mobile telephone for health-related issues (aOR = 1.476, 95%CI = 1.02–2.14, p-value = 0.04) slightly increase the chance of attending adequate visits. Conclusion This study identified determinants influencing ANC visits. ANC booking, using the Internet, and mobile phones enhance the likelihood of completing recommended ANC visits while higher parity and experiencing partner-related sexual violence decrease these chances. These findings show a need for addressing wealth inequality, geographical barriers, the impact of intimate partner violence, encouraging internet access for health information, and health promotion for early ANC booking to improve the uptake of ANC services.